If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1n + 7n = 18 Combine like terms: -1n + 7n = 6n 6n = 18 Solving 6n = 18 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Divide each side by '6'. n = 3 Simplifying n = 3
| x^2+29x+79=0 | | 9x-29/10 | | 4(m-s)=24 | | 2(4z-5-3)=166-48 | | x+41=-90 | | 2/3x5/1 | | Y-4=-1/4(x-3) | | x+41= | | (-6)+(6)= | | 8x=-120/18 | | 40+3a=-5 | | 3(3x-6)=-(x-2) | | -2/3u=-4 | | (X-8)(3x+10)=0 | | 7w+54=61 | | 12x-3x^2+42= | | -21=-7/5x | | 4e+0.625=3.125 | | 5k-12=-4K+15 | | 5x^2+28x= | | 5(4-x)=15 | | -12-28-5x=-30 | | 4x^5-x^7= | | 32y^2+48y-16=0 | | 3s+17=56 | | 65(t)=-16t^2+85t+1 | | 3(y-5)=7 | | 10x+7y-50=150 | | 5p+p=54 | | -3y-18=3 | | -18t-6t+8=-16 | | t/5-7=-12 |